Matrine Attenuates COX-2 and ICAM-1 Expressions in Human Lung Epithelial Cells and Prevents Acute Lung Injury in LPS-Induced Mice - Chian-Jiun Liou; You-Rong Lai; Ya-Ling Chen; Yi-Hsien Chang; Zih-Ying Li; Wen-Chung Huang (Mediators of Inflammation)
Matrine is isolated from Sophora flavescens and shows anti-inflammatory effects in macrophages. Here we evaluated matrine’s suppressive effects on cyclooxygenase 2 (COX-2) and intercellular adhesion molecule-1 (ICAM-1) expressions in lipopolysaccharide- (LPS-) stimulated human lung epithelial A549 cells. Additionally, BALB/c mice were given various matrine doses by intraperitoneal injection, and then lung injury was induced via intratracheal instillation of LPS. In LPS-stimulated A549 cells, matrine inhibited the productions of interleukin-8 (IL-8), monocyte chemotactic protein-1, and IL-6 and decreased COX-2 expression. Matrine treatment also decreased ICAM-1 protein expression and suppressed the adhesion of neutrophil-like cells to inflammatory A549 cells. In vitro results demonstrated that matrine significantly inhibited mitogen-activated protein kinase phosphorylation and decreased nuclear transcription factor kappa-B subunit p65 protein translocation into the nucleus. In vivo data indicated that matrine significantly inhibited neutrophil infiltration and suppressed productions of tumor necrosis factor-α and IL-6 in mouse bronchoalveolar lavage fluid and serum. Analysis of lung tissue showed that matrine decreased the gene expression of proinflammatory cytokines, chemokines, COX-2, and ICAM-1. Our findings suggest that matrine improved lung injury in mice and decreased the inflammatory response in human lung epithelial cells.